2007
DOI: 10.1111/j.1872-034x.2007.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of N‐acetylcysteine and metformin improves histological steatosis and fibrosis in patients with non‐alcoholic steatohepatitis

Abstract: Based on the biochemical and histological evidence in this pilot study, NAC in combination with MTF appears to ameliorate several aspects of NASH, including fibrosis. Further studies of this form of combination therapy are warranted to assess its potential efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 42 publications
5
58
0
3
Order By: Relevance
“…248 Patients with NAFLD have had better histologi-cal activity scores and less hepatic fibrosis after treatment with N-acetylcysteine and metformin. 110 Similar anti-fibrotic actions have been demonstrated after therapy with other anti-oxidants (SAMe and vitamin E) (Figure 1). 59,89,250 Mortality or the need for liver transplantation has decreased from 29% to 12% in patients with alcoholic cirrhosis who have been treated with SAMe, 242 and this treatment has also increased the frequency of an early virological response in otherwise non-responsive patients with chronic hepatitis C (genotype 1).…”
Section: Inhibitors Of Oxidative Stress As Anti-fibrotic Agents In Ausupporting
confidence: 62%
“…248 Patients with NAFLD have had better histologi-cal activity scores and less hepatic fibrosis after treatment with N-acetylcysteine and metformin. 110 Similar anti-fibrotic actions have been demonstrated after therapy with other anti-oxidants (SAMe and vitamin E) (Figure 1). 59,89,250 Mortality or the need for liver transplantation has decreased from 29% to 12% in patients with alcoholic cirrhosis who have been treated with SAMe, 242 and this treatment has also increased the frequency of an early virological response in otherwise non-responsive patients with chronic hepatitis C (genotype 1).…”
Section: Inhibitors Of Oxidative Stress As Anti-fibrotic Agents In Ausupporting
confidence: 62%
“…Results with metformin (a biguanide) have been heterogeneous, most studies have been small and have flaws in the design, and its effect may be largely related to its ability to induce weight loss. [134][135][136][137][138] Data with thiazolidinediones (pioglitazone, troglitazone, and rosiglitazone) for the treatment of NASH are more robust. [139][140][141][142] However, it is unclear whether a thiazolidinedione-associated increase in adiposity and weight gain would ultimately limit its benefits.…”
Section: Prevention and Management Of Haart Liver Toxicitymentioning
confidence: 99%
“…Human studies have documented a reduction in aminotransferases with metformin. [6][7][8][9][10][11] However, alanine aminotransferase (ALT) breakthrough was reported, 12 suggesting that there is no sustained effect. Other 1-year trials showed no overall significant reduction in ALT values.…”
Section: Efficacy Outcomes In Nashmentioning
confidence: 99%